2020
DOI: 10.1002/ange.202004747
|View full text |Cite
|
Sign up to set email alerts
|

Kalium‐Polyheptazinimid: Ein übergangsmetallfreier Festkörper‐Triplett‐Sensibilisator in Kaskadenenergietransfer und [3+2]‐Cycloadditionen

Abstract: Polymere Kohlenstoffnitridmaterialien wurden erfolgreich in zahlreichen Anwendungen zur Umwandlung von Licht in Energie, die von der Photokatalyse bis zur Optoelektronik reichen, eingesetzt. Für eine neue Anwendung und Modellierung verfeinerten wir zunächst die Kristallstruktur von Kalium‐Polyheptazinimid (K‐PHI) – einem Referenz‐Kohlenstoffnitridmaterial in der Photokatalyse – mithilfe von Röntgenpulverdiffraktometrie und Transmissionselektronenmikroskopie. Unter Verwendung der Kristallstruktur von K‐PHI wurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 64 publications
(122 reference statements)
2
35
0
3
Order By: Relevance
“…[ 42 ] As is indeed the case in this study, cooling the sample splits the reflection corresponding to d = 1.65 Å into two peaks as indicative of symmetry being reduced from a strictly planar hexagonal space group, and the best structural model from subsequent Rietveld refinement shows slight non‐planarity in the triazine layers. For PHI as another example, describing the stacking structure is one problem [ 44 ] that can be tackled by combined PDF and XRD analyses, which show how its pore constituents—the water molecules and potassium ions—mediate the stacking of the PHI layers in the 3D. [ 29d ] Here, within the pores of the PHI, the water‐solvated potassium cations as incorporated from the salt melt synthesis strongly interact with the PHI layers, providing a directing effect on the layer stacking resulting in slip‐stacked layers; conversely, removal of these cations (e.g., by exchange with protons) leads to more defective stacking owing to the weaker interactions between the PHI layers.…”
Section: Characterization Methodologies From Molecular Structure To O...mentioning
confidence: 99%
“…[ 42 ] As is indeed the case in this study, cooling the sample splits the reflection corresponding to d = 1.65 Å into two peaks as indicative of symmetry being reduced from a strictly planar hexagonal space group, and the best structural model from subsequent Rietveld refinement shows slight non‐planarity in the triazine layers. For PHI as another example, describing the stacking structure is one problem [ 44 ] that can be tackled by combined PDF and XRD analyses, which show how its pore constituents—the water molecules and potassium ions—mediate the stacking of the PHI layers in the 3D. [ 29d ] Here, within the pores of the PHI, the water‐solvated potassium cations as incorporated from the salt melt synthesis strongly interact with the PHI layers, providing a directing effect on the layer stacking resulting in slip‐stacked layers; conversely, removal of these cations (e.g., by exchange with protons) leads to more defective stacking owing to the weaker interactions between the PHI layers.…”
Section: Characterization Methodologies From Molecular Structure To O...mentioning
confidence: 99%
“…The PHI layers are aligned directly on top of each other forming continuous channels along the c direction (AAA stacking). [ 6 ] Analysis of both HR‐TEM and SAED data shows that nanocrystalline domains tend to be preferentially oriented in the flack along the c direction of the structure, but possess rotational disorder in the ab plane.…”
Section: Resultsmentioning
confidence: 99%
“…This approach facilitates the investigation of the complementary oxidation/reduction reaction (e.g., proton reduction to H 2 and water oxidation to O 2 ). [ 4 ] The scavenging process can, however, create a strong kinetic asymmetry in the carrier extraction from the light absorber, resulting in the accumulation of one type of charge, [ 5,6 ] as detailed in Figure . This charge accumulation process may generate bottlenecks in the hydrogen evolution reaction (HER) photocatalyzed by carbon nitride‐based materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that Equation (6) overestimates real S SA of materials, since it does not take into account possible sintering of particles. If not available in the reference article, the following gravimetric density of materials was used: ZnO 5.6 g cm −3 , TiO 2 3.9 g cm −3 (amorphous, anatase), K‐PHI 1.88 g cm −3 (X‐ray density), [ 39 ] H‐PHI 1.39 g cm −3 (X‐ray density), [ 38 ] gCN (when crystal structure was not explicitly specified) 2.2 g cm −3 , In 2 O 3 6.75 g cm −3 , CeO 2‐ x 7.13 g cm −3 , CdSe 5.3 g cm −3 , and WO 3 7.2 g cm −3 . Gravimetric density of hybrid composites made of SCPs and metal nanoparticles or two semiconductors was calculated taking into account a fraction and gravimetric density of each component.…”
Section: Database Of Photocharged Materialsmentioning
confidence: 99%
“…determined that in potassium poly(heptazine imide) (K‐PHI, Figure 3b) K + ions are located closer to the center of the channels and in between layers. [ 39 ] Sahoo et al. modeled structures of several metal poly(heptazine imide)s and found that in K‐PHI and Mg‐PHI cations are in the pores between the layers, while in Au‐PHI and Ru‐PHI cations are in the same plane with PHI layer.…”
Section: Introductionmentioning
confidence: 99%